Xenoimplant of Collagen Matrix Scaffold in Liver Tissue as a Niche for Liver Cells - Martinez-Castillo, Moises; León-Mancilla, Benjamín; Ramírez-Rico, Gerardo; Alfaro, Ana; Pérez-Torres, Armando; Díaz-Infante, Daniela; García-Loya, Jorge; Medina-Avila, Zaira; Sanchez-Hernandez, Jaime; Piña-Barba, Cristina; Gutierrez-Reyes, Gabriela (Frontiers in Medicine, 2022)
Liver damage induced by hepatitis C virus, chronic liver damage due to alcohol, and nonalcoholic liver disease-induced cellular alterations promotes fibrosis, cirrhosis and/or hepatocellular carcinoma. The recommended therapeutic option for advanced liver damage is liver transplantation. Extracellular matrix scaffolds have been evaluated as an alternative for tissue restoration. Studies on the biocompatibility and rejection of synthetic and natural scaffolds, as an alternative to organ transplantation, have been evaluated. Our group has recently described the xenoimplant of collagen matrix scaffold (CMS) in a rat model. However, there has not been a complete macroscopic and histologic description of the liver parenchyma at the initial (day 3), intermediate (day 14), and advanced (day 21) stages. We describe and compare here in liver tissue present in CMS zone (CZ, CMS plus liver parenchyma), liver tissue from the normal zone (liver parenchyma close to the CMS) and basal tissue (resected tissue from the CMS implantation site). Our data strongly suggest that the collagen matrix xenoimplant is a good niche for hepatocytes with no rejection and does not affect liver function tests. The liver can regenerate after damage, but this capacity is inhibited in chronic injury. Until now, the use of CMS, after liver damage, has not been reported. This biomaterial could be a novel alternative in the field of regenerative medicine in liver diseases